The Role of Financial Technology on Income in Small and Medium Enterprises (SMEs) - Eri Yanti Nasution (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2021)
This paper examines the effect of the application of financial technology on SMEs income in Medan. Sampling using the accidental sampling method as many as 100 SMEs in Medan. The method of data collection is by distributing online questionnaires. The method of data analysis in this study used regression analysis. The results of the analysis explain that the application of financial technology influences the income of SMEs in Medan.